Reprints of Rare Papers on Mollusca: Minutes of the Conchologigal Club of Southern California, Nos. 1–10 (Hello World!, 1972)
During their twenty years of existence, the Minutes demonstrated the usefulness of informal publications. The distribution increased considerably with the years and the demand for early numbers grew in proportion. Complete sets of the original Minutes are very scarce and their reprinting here has the twofold purpose of making the earliest numbers available and of paying tribute to John Q. and Rose Burch to whom all malacologists are indebted for their work of editing and printing the Minutes for twenty years. The editor of Sterkiana is personally grateful to the Burches for permission to reprint the Minutes. This is only one of many courtesies and kindnesses which have been received from them by the writer.